GLYCEMIC HOMEOSTASIS OF SMALL AND NORMAL LITTER DURING RAT ADOLESCENCE - Scarlett Rodrigues Raposo; Lucas Paulo Jacinto Saavedra; Maria Natália Chimirri Peres; Rafael Pereira Lopes; Marcos Vinícius Martins; Filipe Lima dos Santos; Willian Nascimento de Souza Rodrigues; Maryana Debossan Fernandes; Mariana Narciso Constancio; Gabriel Kian Guimaraes Lopes; Letícia Ferreira Barbosa; Kérolym Lomes da Cruz,; et al. (Arquivos do Mudi, 2023)
Childhood obesity has become a public health concern, as it leads to cardiometabolicdisorders. The Developmental Origins of Health and Disease (DOHaD) concept shows thatinsults in critical windows of development can program the individual for both health anddisease. In the neonatal supernutrition model, known as small litter (SL), the litter is reducedto 3 animals per dam, mimicking obesity, while the normal litter (NL) control animals haveonly 9 animals per dam. The period of adolescence in SL animals is still little explored, it isknown that in this phase there are many hormonal changes, but it is still not known how thebehavior is in relation to glycemia, so our objective was to evaluate glycemia during thetolerance test oral glucose in NL and SL animals during adolescence. It is observed that theNL and SL animals show no difference in glucose tolerance at 45 and 60 days. However, bothgroups are glucose intolerant when compared to their respective controls in adult life. Weconclude that there is glucose intolerance during adolescence regardless of the nutritionalinsult.